Educating Social Workers for Practice in Integrated Health Care: A Model Implemented in a Graduate Social Work Program. (17th July 2017) - Mattison, Debra; Weaver, Addie; Zebrack, Brad; Fischer, Dan; Dubin, Leslie
ABSTRACT: This article introduces a curricular innovation, the Integrated Health Scholars Program (IHSP), developed to prepare master's-level social work students for practice in integrated health care settings, and presents preliminary findings related to students' self-reported program competencies and perceptions. IHSP, implemented in a research-intensive school of social work in a large midwestern public university, includes specialized course work, interprofessional education across health science disciplines, and field practicum in integrated health care settings. Curricular components support stepwise learning and follows the British Columbia model of interprofessional education learning tiers: exposure, immersion, and skill mastery. Despite IHSPs successful development in a well-resourced, supportive environment, challenges facing our profession's ability to develop and sustain training of MSW students in integrated health care are discussed.